ALTERATIONS OF GUT MICROBIOTA AND SHORT-CHAIN FATTY ACID IN PATIENTS INFECTED WITH HEAVY STRONGYLOIDES STERCORALIS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the changes of gut microbiota and acetic acid in patients with different levels of Strongyloides stercoralis- infected.Methods: This study was conducted on the farmers in the Northeastern region of Thailand. Fifty patients infected with S. stercoralis were divided into two groups, SA and SF.The SA group included patients in whom S. stercoralis was detected only by the agar plate culture method, whereas the SF group included patients in whom the parasite was detected by both agar plate culture and the formalin–ether concentration technique. Bacterial DNA was extracted from individual faecal samples and was then pooled into two groups (SA and SF) for amplification and sequencing of the V3-V4 region of the 16S gene with next-generation technology. Acetic acid in blood was determined by gas chromatography-mass spectrometry GC-MS.Results: The results showed that the intensity of S. stercoralis infection was associated with alterations in the gut microbiota and acetic acid levels. Compared with the mildly infected group (SA), the severely infected group (SF) exhibited a significant reduction in acetic acid levels, accompanied by a marked decrease in beneficial bacterial genera, including Bifidobacterium, Lactobacillus, and Blautia. In contrast, potentially pathogenic genera such as Escherichia–Shigella, Proteus, and Bacteroides were significantly increased in the SF group. Notably, several beneficial short-chain fatty acid–producing bacterial species, including Coprococcus eutactus, Lactobacillus salivarius, and Lactobacillus reuteri, were markedly reduced in severely infected patients, indicating gut microbiota dysbiosis associated with infection intensity.Conclusion: Heavy S. stercoralis infection reduced beneficial intestinal bacteria and acetic acid in patients.
Keywords: Strongyloides stercoralis, 16sRNA gene, formol-ether concentration technique, agar plate culture, short-chain fatty acids.